Open Benchmarking Platform for Data Inversion Methods - Gorman, Gerard; Luporini, Fabio; St-Cyr, Amik; Loddoch, Alexander; Souza, A.; Witte, Philipp; Hester, Ken; Dupros, Fabrice; Araya, Mauricio (Sixth EAGE High Performance Computing Workshop, 2022)
Taking inspiration from success stories such as the SEAM Open Data, we bring together expertise from multiple institutions to devise a platform that provides a trustworthy representation of the challenges in real-life seismic inversion.